Basalt waste management in the production of highly effective porous polyurethane composites for thermal insulating applications. (July 2019) - Kurańska, Maria; Barczewski, Mateusz; Uram, Katarzyna; Lewandowski, Krzysztof; Prociak, Aleksander; Michałowski, Sławomir
Abstract: The aim of this work was to evaluate the influence of waste basalt powder (BP) on selected properties of rigid polyurethane foams (PUR). The application of BP allowed a reduction of the content of the polymer matrix while maintaining good functional properties of the foams for thermal insulation purposes. The polyurethane/basalt composites were obtained using BP as a filler in amounts from 3 to 40 wt% respectively to the total polyurethane components. It was observed that BP caused an increase in the reactivity of polyurethane system during the foaming process, which was also confirmed by dielectric polarization changes. The thermal conductivity of the materials obtained was in the range 22.25–25.10 mW/m·K. Incorporating BP caused a decrease in the mechanical properties. However, polyurethane composite foams evaluated by dynamic mechanical thermal analysis displayed improved thermomechanical stability. Basalt filler also provided an improvement of the thermal stability of polyurethane. Highlights: Basalt powder (BP) was used for the production of polyurethane composite foams. Inorganic filler significantly influence polyurethane (PUR) properties. Catalytic behaviour of BP on PUR allow to obtain highly-filled porous composites. The addition of BP into PUR is an effective way of mining waste management. New method of solid waste management in polymer synthesis was presented.